Microwave-assisted solvent-free synthesis of 3-benzylideneindolin2-one and investigation of in-vitro anti-fungal and antioxidant activities - Wijekoon, H.P.S.K.; Jayaweera, P.P.M.; Gunasekara, T.D.C.P.; Fernando, S.S.N.; Palliyaguru, N.P.L.N.; Kumarasinghe, K.G.U.R. (My University, 2021)
Background: Synthesis and biological investigations of 3-benzylideneindolin-2-ones has stirred interest in pharmaceutical field due to its privileged scaffold oxindole. These oxindole derivatives have a broad spectrum of biological activities including anti-cancer, anti-viral, anti-bacterial, anti-oxidant and anti-inflammatory. Microwave-assisted organic reactions in solvent-free conditions has many advantages over conventional methods such as higher atom- economy, E-factor and product purity. Objectives: Microwave-assisted solventfree synthesis of 3-benzylidineindolin-2-one and investigation of anti-fungal and anti-oxidant activities. Methods: Oxindole and benzaldehyde is thoroughly mixed with (3-Aminopropyl) triethoxysilane (APTES) functionalized silica catalyst and irradiatedinside the modified microwave oven for 12 minutes. After completion of the reaction the resulting products wereextracted to a mixture of ethanol, acetone and ethyl acetate (1: 1: 1: v/v) and subsequently purified by column chromatography. Resulted product was characterized by Nuclear Magnetic Resonance spectroscopy (1H NMR and13C NMR), Fourier-Transform Infrared spectroscopy (FTIR) and melting point analysis. The compound was tested for in-vitro antifungal activity against Candida albicans(ATCC 10231) and Candida krusei (ATCC 6258) using welldiffusion assay and broth micro dilution assay. Anti-oxidant activity of the compound was investigated using 2,2-azino-bis(3-ethylbenzothiazoline-6- sulfonic acid (ABTS) assay Results: Melting point of the synthesized 1H NMR, 13C NMR and FTIR data confirms theformation of targeted 3-Benzylideneindolin-2-ones and has an agreement with the reported data in the literature. Themean zones of inhibition (ZOI) of the compound and the positive control miconazole against Candida albicansandCandidakrusei were 20.0 mm, 18.33 mm and 14.6 mm and 22.6 mm respectively. Both minimum inhibitoryconcentration and minimum fungicidal concentration of the compound against Candida albicans and Candida krusei respectively. The concentration at 50% inhibition (IC-50) of the compound was 0.2mg/mL
Keywords: These findings revealed that 3-benzylidene-indolin-2-one shows strong anti-fungal and anti-oxidant activity.